Catalyst and method for producing methanol using the same

A catalyst combining p-type and n-type semiconductor oxides efficiently converts carbon dioxide to methanol, addressing inefficiencies in existing methods by promoting selective hydrogenation and suppressing by-product formation.

JP2025171178APending Publication Date: 2025-11-20MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024076246
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-11-20

AI Technical Summary

Technical Problem

Existing methods for synthesizing methanol from carbon dioxide are inefficient and produce unwanted by-products like carbon monoxide and methane, leading to low methanol selectivity and increased reactor complexity.

Method used

A catalyst composed of a p-type semiconductor oxide and an n-type semiconductor oxide, represented by specific formulas, is used to selectively convert carbon dioxide to methanol without producing by-products, leveraging their electrical conductivity and electron transfer properties to promote efficient hydrogenation.

Benefits of technology

The catalyst achieves high methanol selectivity and efficiency under mild conditions, suppressing side reactions and maintaining electrical conductivity, thereby enhancing the production of methanol from carbon dioxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025171178000002
    Figure 2025171178000002
  • Figure 2025171178000003
    Figure 2025171178000003
  • Figure 2025171178000004
    Figure 2025171178000004
Patent Text Reader

Abstract

To provide a catalyst capable of selectively generating methanol through hydrogenation of carbon dioxide, and an efficient method for producing methanol employing the catalyst.SOLUTION: A catalyst comprising a material in which a semiconductor oxide represented by Formula (1) and a semiconductor oxide represented by Formula (2) are joined. Formula (1): AJaOm. Formula (2): DOnXx.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a catalyst and a method for producing methanol using the catalyst, and in particular to a method for efficiently producing carbon dioxide The present invention relates to a catalyst and a production method for producing methanol by hydrogenating carbon. A solid catalyst is used that combines a type semiconductor oxide and an n-type semiconductor oxide, and the catalyst Carbon dioxide is hydrogenated and converted into methanol by contacting it with hydrogen. Regarding technology. [Background technology]

[0002] Carbon dioxide is a stable compound, but its chemical transformation requires the use of energy and hydrogen. However, with the help of catalysts, heat, pressure, etc., it is possible to convert it quickly in a limited space. In the process of hydrogenating carbon dioxide using a catalyst, the product is mono-acid Possible reaction methods include carbon monoxide, formic acid, formalin, methanol, and methane, and the appropriate reaction technology for each is available. However, the reaction mechanisms of each have not been fully elucidated. It is still insufficient in terms of efficiency.

[0003] The most attractive of these target products is methanol. is a liquid at room temperature, so it fixes carbon dioxide gas, which causes global warming, in a liquid state. Furthermore, methanol is chemically reactive, so methanol Useful chemical products can be produced by chemical conversion of raw materials. This is because nol can be used not only as fuel but also as a resource for chemical production.

[0004] The synthesis of methanol from carbon dioxide requires the presence of a catalyst, and copper is a widely known catalyst. In addition to zinc-based oxides (Patent Documents 1 and 2), various catalysts have been reported in recent years. For example, a catalyst in which palladium is supported on indium oxide (Non-Patent Document 1), a catalyst in which zirconium oxide is supported on Catalysts such as a catalyst in which indium oxide is supported on a catalyst (Non-Patent Document 2) have been reported. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 45-016682 [Patent Document 2] Japanese Patent Application Publication No. 49-017391 [Non-patent literature]

[0006] [Non-Patent Document 1] APPLIED CATALYSIS B: ENVIRONMENTAL, 218, 2017, 488-497 [Non-patent document 2] Angew.Chem.Int.Ed.2016, 55, 6261-6265 Summary of the Invention [Problem to be solved by the invention]

[0007] However, from an economic point of view, the method of synthesizing methanol from carbon dioxide is still not effective. It is clear that there are problems in terms of efficiency. A catalyst for the direct production of methanol from carbon dioxide in the hydrogenation of carbon dioxide, i.e. Therefore, a catalyst is needed that can selectively convert carbon dioxide to methanol without producing carbon monoxide or methane as by-products. Even if the conversion rate is low, if the methanol selectivity is high, it is possible to increase the amount of catalyst or the reaction temperature. Efficiency can be improved by increasing the speed. Copper-zinc oxide catalysts are believed to be active in this reaction, and there are no issues with the catalyst. However, conventional copper-zinc oxide catalysts are not suitable for the production of methanotrophic catalysts by hydrogenating carbon monoxide. This catalyst was developed for methanol synthesis, and when carbon dioxide is hydrogenated, methanol is produced. The reason for the low methanol selectivity in copper-zinc oxide catalysts is The reverse water gas shift reaction of carbon dioxide to carbon monoxide occurs, and This is because a reaction occurs between alcohol and carbon monoxide and hydrogen, but a large amount of carbon monoxide is produced as a by-product. If we were to recycle these materials instead of incinerating them, the process would become more complicated and This requires a larger reactor.

[0008] Furthermore, the present inventors have reported that the hydrogenation of carbon dioxide using a known catalyst other than a copper-zinc oxide catalyst When the reaction was carried out, the carbon dioxide conversion rate and methanol selectivity were low and not satisfactory. In order to efficiently obtain methanol from carbon dioxide, the hydrogenation of carbon dioxide was In this case, a catalyst for direct production of methanol from carbon dioxide is used. A catalyst that selectively converts carbon dioxide to methanol without producing by-products, and a thermodynamic equilibrium There has been a demand for a method for synthesizing methanol more selectively at low temperatures, which are advantageous in . The present invention has been made in view of the above circumstances, and its object is to provide a method for hydrogenating carbon dioxide. for selectively producing methanol by ethanol synthesis and efficient methanol production using the same - Patents.com The object is to provide a manufacturing method. [Means for solving the problem]

[0009] The present inventors have considered the reaction mechanism of the reduction of carbon dioxide with hydrogen and have found that the reduction of carbon dioxide with methanol The catalyst required for converting carbon dioxide into hydrogen is the ability to take away one oxygen atom. and the oxygen is reduced to water, and at the same time, the remaining carbon is reduced. It is important that they have the function of promoting the supply of electrons and that they exist in the same particle of the catalyst. It was also found that hydrogen activation ability, oxygen depletion ability, electron supply ability, and electrical conductivity were important. The oxidizing site that takes electrons from hydrogen and the reducing site that provides electrons to carbon dioxide are separated. While focusing on the structure that maintains electrical conductivity between the two, we explored the relationship between the composite of each component and catalytic performance. Surprisingly, a structure in which a p-type semiconductor oxide and an n-type semiconductor oxide are joined together was found. The inventors have found that it is an excellent catalyst, which has led to the present invention. That is, the present invention is summarized as follows: [1] to [7].

[0010] [1] A semiconductor oxide represented by the following formula (1) and a semiconductor oxide represented by the following formula (2) A catalyst comprising a material having a bonded AJ a O m (1) (In the formula (1), Component A is a minor element selected from the group consisting of Cu, Pd, Pt, Rh, Ru, Ir, and Ag. It represents at least one element, The constituent elements J are Fe, Ni, Mn, Co, Cr, Y, Sc, Ce, La, Al, Ga and and In, The component O represents oxygen, a and m represent the molar ratios of J and O to A, respectively, and 0 <a≦3、0.5<m≦4を It is a satisfactory number.) DO n X x (2) (In the formula (2), Component D is at least one selected from the group consisting of In, Ga, Al, B, Zn and Sn. It represents a type of element, The component O represents oxygen, Constituent X is P, S, Se, Te, Sb, Bi, Pb, Cl, I, F, H, C, Si and and Ge, n and x represent the molar ratios of O and X to D, respectively, and 0 <n≦1.5、0≦x≦1を It is a satisfactory number.)

[0011] [2] X-ray diffraction measurement XRD (CuKα) at ​​a diffraction angle (2θ) of 20° to 70° The range has diffraction peaks characteristic of the delafossite structure, as described in [1]. Catalyst. [3] Volume resistivity of 1.0x10 under a pressure of 20kN at 25°C 10 Ω·cm or less The catalyst according to [1] or [2].

[0012] [4] It is obtained by heat treatment at 100°C or more and 1200°C or less, [1]~[3 ] The catalyst according to any one of the preceding items. [5] The hydrogenation of oxygen-containing compounds, as described in any one of [1] to [4]. Catalysts listed. [6] The catalyst according to [5], wherein the oxygen-containing compound is carbon dioxide. [7] The hydrogenation reaction of carbon dioxide at temperatures between 50°C and 400°C was carried out using the methods [1] to [6]. A method for producing methanol, using the catalyst according to any one of claims 1 to 4. [Effects of the Invention]

[0013] According to the present invention, a catalyst and a catalyst for selectively producing methanol by hydrogenating carbon dioxide are provided. It is also possible to provide an efficient method for producing methanol using the same. [Brief explanation of the drawings]

[0014] [Figure 1] 1 is an XRD chart of the catalyst obtained in Example 1. [Figure 2] 1 is an XRD chart of the catalyst obtained in Example 9. [Figure 3] 1 is an XRD chart of the catalyst obtained in Example 11. DETAILED DESCRIPTION OF THE INVENTION

[0015] The following describes in detail the embodiments of the present invention. These are merely examples (typical examples), and the present invention is not limited to these contents as long as it does not exceed the gist of the invention. do not have.

[0016] [catalyst] The catalyst of the present invention is a semiconductor oxide AJ represented by the following formula (1): a O m and in the following equation (2): The semiconductor oxide represented by DO n X x By using this catalyst, This makes it possible to hydrogenate carbon dioxide under mild conditions.

[0017] AJ a O m (1) (In the formula (1), Component A is a minor element selected from the group consisting of Cu, Pd, Pt, Rh, Ru, Ir, and Ag. It represents at least one element, The constituent elements J are Fe, Ni, Mn, Co, Cr, Y, Sc, Ce, La, Al, Ga and and In, The component O represents oxygen, a and m represent the molar ratios of J and O to A, respectively, and 0 <a≦3、0.5<m≦4を It is a satisfactory number.)

[0018] DO n X x (2) (In the formula (2), Component D is at least one selected from the group consisting of In, Ga, Al, B, Zn and Sn. It represents a type of element, The component O represents oxygen, Constituent X is P, S, Se, Te, Sb, Bi, Pb, Cl, I, F, H, C, Si and and Ge, n and x represent the molar ratios of O and X to D, respectively, and 0 <n≦1.5、0≦x≦1を It is a satisfactory number.)

[0019] AJ in Eq. (1) a O m and DO of Eq. (2) n X x The bonded material is effective as a hydrogenation catalyst. One of the reasons for its effectiveness is that AJ has the ability to activate hydrogen and remove charge from hydrogen. a O m is expressed as Occurs on p-type semiconductor oxide, activating carbon dioxide by removing oxygen from it and reducing carbon dioxide. Function DO n X x The suppression of side reactions occurring on n-type semiconductor oxides, represented by Furthermore, the transfer of charge between the two is rectified smoothly by the semiconductor junction. The high electrical conductivity between the two also contributes to the efficient reaction. In particular, n-type semiconductor oxide DO n X x In (indium) as D In materials containing In, the spatially extended s orbital of In constitutes part of the conduction band, so they are crystalline. Even in a poor amorphous structure (atoms not regularly arranged), electrons can still flow. A conductive band is formed, which promotes the supply of electrons obtained from hydrogen and makes the reduction reaction more efficient. It is thought that the disease will progress in a systematic manner.

[0020] The catalyst of the present invention is a catalyst obtained by bonding a semiconductor oxide of the formula (1) and a semiconductor oxide of the formula (2). There is no particular limitation as long as it includes a material bonded to the substrate (hereinafter sometimes referred to as "bonding material"). The adhesive may contain components of the molded body such as a support, carrier, binder, etc. other than the bonding substance. Specifically, the bonding material may be supported on the carrier described below or may be physically mixed with the carrier described below. You may do so.

[0021] The type of the support is not particularly limited, but is usually SiO2, GeO2, Al2O3, Re2 O7, Cr2O3, ZnO, MgO, CaO, BaO, ZrO2, TiO2, CeO2, SnO2, ITO, STO, BTO, SiC, activated carbon, graphite, carbon, etc. Preferably, SiO2, GeO2, Cr2O3, ZnO, ZrO2, T iO2, CeO2, SnO2, ITO, STO, BTO, and SiC, and more preferably , ZnO, Cr2O3, ZrO2, TiO 2、 The support is powder or pellets. The bonding material and the carrier may be mixed, or may be in the form of paper or a substrate. It may also be used as a form.

[0022] The proportion of the bonding material in the catalyst is not particularly limited as long as it is within a range that does not impair the effects of the present invention. However, the amount of the bonding material relative to the entire catalyst is usually 5% by mass or more, preferably 10% by mass or more. The upper limit is not particularly limited, and it is preferably 100% by mass. It is also possible.

[0023] The catalyst of the present invention has a delafossite structure, which is known as a type of p-type semiconductor. Preferably, the semiconductor oxide represented by the formula (1) has a delafossite structure. When the semiconductor oxide represented by the formula (1) has a delafossite structure, The element A exists as a monovalent cation, and has excellent performance as a p-type semiconductor (hole carrier concentration, Hall mobility, and electrical conductivity). From this viewpoint, the catalyst of the present invention has a diffraction angle ( 2θ) in the range from 20° to 70°, there are diffraction peaks characteristic of the delafossite structure of AJO2. It is preferable that the diffraction peak has a JCPDS card number. No. 035-1402, 39-0247, 39-0246, 50-0860, 39-02 44 and the like.

[0024] One of the advantages of the catalyst of the present invention containing a substance with a delafossite structure as a p-type semiconductor is that The p-type semiconductor mainly dissociates and activates hydrogen to oxidize it (removing charge) and at the same time, the electrical conductivity Because it has electrical conductivity, it transfers the charge obtained by the oxidation of hydrogen to carbon dioxide. The advantage is that it becomes easier to supply the n-type semiconductor, which is responsible for the reduction of the In the site structure, the element A exists stably as a monovalent cation, and it is a p-type semiconductor. Therefore, the above characteristics are maintained for a long period of time and side reactions are suppressed. The reaction of carbon dioxide to methanol continues efficiently.

[0025] The catalyst of the present invention preferably has a relatively high surface area, as measured by the BET method. If expressed as a specific surface area that can be measured, it is preferably 1 m 2 / g or more, more preferably 5m2 / g or more , more preferably 10 m 2 / g or more, particularly preferably 20m 2 / g or more, and Approximately 300m 2 / g or less, more preferably 250m 2 / g or less, more preferably 200 m 2 / g or less, particularly preferably 175m 2 / g or less. If the surface area is large enough, This ensures sufficient contact with gas phase molecules, allowing the catalytic reaction to proceed efficiently. The size of the particles is within a range that allows the particles to adsorb carbon dioxide. As a result, the electrons required for reduction are met. The reduction reaction to methanol is promoted, and high selectivity to methanol is maintained. If the size is within a certain range (if it is not too large), the number of surface defects is suppressed and the conductive The electrical conductivity is no longer impaired by phenomena such as electrons being trapped in defects. This keeps the reduction reaction going.

[0026] <Joining material> (A.J. a O m ) AJ a O m The amount is not particularly limited, but is preferably 0.01 wt % relative to the total amount of the bonding material. 1% by mass or more, more preferably 2% by mass or more, even more preferably 5% by mass or more, and particularly preferably The content is preferably 10% by mass or more, and more preferably 90% by mass or less, and more preferably 80% by mass or less. % by mass or less, more preferably 70% by mass or less, and particularly preferably 60% by mass or less. These ranges allow for a balance between the acquisition of charge by hydrogen activation and the generation of water by hydrogen oxidation. Lance is the preferred range.

[0027] AJ a O m The component A in the AJ plays an important role in forming the p-type semiconductor oxide. a O m It is preferable that A exists mainly as a monovalent cation in the (The standard electrode potential is more positive than hydrogen) Cu, Pd, Pt, Rh, Ru, Ir, Ag At least one element selected from the group consisting of Cu, Pd, Rh, Ir, At least one element selected from the group consisting of Cu, Pd, At least one element selected from the group consisting of Ag. a O m A of It is known that delafossite structure compounds containing Cu, Pd, and Ag can be synthesized using this method. The delafossite structure compound also has similar functions as an excellent p-type semiconductor. It is known that two or more types of A may be used. AJ a O m The valence of A in the It can be evaluated by ES (near edge structure). a O m A exists as a single value in The proportion of A is usually 30 mol % or more, preferably 40 mol % or more, more preferably 10 mol % or more, based on all A's. It is preferably 50 mol % or more, and more preferably 60 mol % or more.

[0028] AJ a O m The component J in the AJ plays an important role in forming the p-type semiconductor oxide. a O m It is preferred that the AJ in the present invention exists as a trivalent cation. a Om J are less easily reduced than protons (their standard electrode potentials are more negative than hydrogen). At least one selected from the group consisting of Cr, Y, Sc, Ce, La, Al, Ga, and In is also a kind of element. a O m As J, Fe, Ni, Mn, Co, Cr, Delafossite structure compounds containing Y, Sc, Ce, La, Al, Ga, and In can be synthesized. It is known that the delafossite structure has excellent properties as a p-type semiconductor. .

[0029] On the other hand, from the viewpoint of catalytic reaction, elements with high deoxidation ability (Fe, N i, Co) promotes excessive reduction reaction to methane, where the element becomes the active site. This tends to increase the likelihood of methanol being present, resulting in a decrease in methanol selectivity. It is not preferable that a large amount of AJ is contained. a O m Component J in the At least one element selected from the group consisting of Mn, Cr, Y, Ce, La, In, Ga, and Al It is also an element, and more preferably, it is selected from the group consisting of Mn, Cr, Y, Ce, and La. At least one element selected from the group consisting of Cr, Y, and Ce is particularly preferred. At least one element selected from the group consisting of J and Zn is used. Multiple types of J may be used.

[0030] AJ a O m The valence of J in the It can be evaluated by ES (near edge structure). a O m J exists as a trivalent The proportion of J is usually 30 mol % or more, preferably 40 mol % or more, more preferably It is preferably 50 mol % or more, and more preferably 60 mol % or more.

[0031] The molar ratio a of component J to component A is greater than 0, preferably 0.2 or more, more preferably Preferably, it is 0.5 or more, more preferably 0.8 or more, and particularly preferably 0.9 or more. , usually 3 or less, preferably 2.5 or less, more preferably 2.0 or less, and even more preferably 1 These ranges ensure the delafossite structure and provide high performance. It acts as a catalyst.

[0032] In addition, a part of A and J may be contained in the catalyst of the present invention as a compound with a metal or X or O in formula (2). It is preferable that they exhibit p-type semiconductivity. By bonding with a compound that exhibits the following, the hydrogenation (reduction) of carbon dioxide proceeds smoothly. In this case, hydrogen activation and carbon dioxide reduction do not occur at the same site on the catalyst particle. However, if the catalyst is composed of semiconducting components, For example, carriers obtained by hydrogen activation can be supplied via the bulk. The reduction reaction is promoted without interfering with the migration of adsorbed hydrogen and adsorbed carbonate on the surface. The reaction of carbon dioxide to methanol proceeds efficiently.

[0033] (m) m is the number of oxygen atoms required to satisfy the valence of each component A and J in formula (1) (A Although not particularly limited, m of a catalyst that exhibits excellent performance is The number of oxygen atoms is slightly less than the number of moles of A that satisfies the oxidation state of J. Usually, the mole ratio of m is greater than 0.5, more preferably 0.8 or greater, and even more preferably 0.9 or greater; It is usually 4 or less, more preferably 3 or less, and even more preferably 2.5 or less. By keeping the temperature within this range, a high surface area and electrical conductivity are maintained, and hydrogen activation and carbon dioxide This balances the reduction of the elements and allows the reaction to proceed efficiently to methanol.

[0034] AJ is a p-type semiconductor a O m There is no restriction on the shape of the crystal, but it is believed to have a delafossite structure. This is because component A exists stably as a monovalent cation and has p-type semiconductor properties. The crystal structure is usually confirmed by XRD (X-ray diffraction).

[0035] AJ a O m One of the advantages of having a delafossite structure as a p-type semiconductor is that Semiconductors mainly dissociate and activate hydrogen to oxidize (remove charge) and at the same time have electrical conductivity. Because it has electrical conductivity, the charge obtained from the oxidation of hydrogen is transferred to the reduction of carbon dioxide. The advantage is that it becomes easier to supply the n-type semiconductor, which carries the The structure has the feature that element A exists stably as a monovalent cation, and it acts as a p-type semiconductor. Therefore, the above characteristics are maintained for a long period of time, and side reactions are suppressed, resulting in the diacid The reaction of oxidized carbon to methanol continues efficiently.

[0036] AJ a O m The electrical conductivity of ―8 S / cm or more, preferably 10 ―6 S / cm or more Above, more preferably 10 ―4 S / cm or more, more preferably 10 ―2S / cm or more, special Preferably 10 ―1 S / cm or more, usually 10 1 S / cm or less. The carrier hole concentration is usually 10 15 / cm 3 More than 10, preferably 16 / cm 3 Below Above, more preferably 10 17 / cm 3 Above, more preferably 10 18 / cm 3 That's all. , usually 10 21 / cm 3 Below is the AJ a O m The electrical conductivity of the catalyst is calculated from the electrical conductivity of the entire catalyst. It is difficult to assess this from the perspective of AJ a O m was prepared separately and its electrical conductivity was evaluated. It is possible to do so. For example, AJ a O m After pressing the powder, electrodes (Pt, etc.) are attached. It can be evaluated by forming it by vapor deposition and then performing hole measurement or the like.

[0037] (DO n X x ) DO n X x The amount of the bonding agent is not particularly limited, but is preferably 100% by mass relative to the total amount of the bonding agent. is 1% by mass or more, more preferably 2% by mass or more, even more preferably 5% by mass or more, and particularly preferably It is preferably 10% by mass or more, more preferably 90% by mass or less, and even more preferably 80% by mass. It is more preferably 70% by mass or less, and particularly preferably 60% by mass or less. In the hydrogenation reaction, the supply of electrons obtained by the activation of hydrogen and the The balance of water production by oxidation falls within a preferred range.

[0038] DO n X x The component D in the n-type semiconductor oxide is the electron It plays a role in reducing carbon dioxide and converting it into methanol using a load. O n X x D is at least one selected from the group consisting of In, Ga, Al, B, Zn and Sn. At least one element is preferably selected from the group consisting of In, Ga, and Zn. More preferably, at least one element selected from the group consisting of In and Ga. It is possible to use multiple types of D. In fact, DO n X x As D, In, Ga, Oxides or composite oxides of Al, B, Zn and Sn have excellent properties as n-type semiconductors. It has.

[0039] The molar ratio of component D to the total number of moles of A, J and D is greater than 0, preferably is 0.01 or more, more preferably 0.02 or more, even more preferably 0.05 or more, More preferably, it is 0.1 or more, particularly preferably 0.2 or more, and preferably 0.8 or less. More preferably, it is 0.7 or less, even more preferably, it is 0.6 or less, and particularly preferably, it is 0.5 or less. Within these ranges, a large surface area is ensured, resulting in a high-performance catalyst.

[0040] DO, an n-type semiconductor n X x There are no restrictions on the form of DO. n However, in the case of In2O3 and ZnO It may be crystalline or non-crystalline (amorphous structure). Usually, their presence can be confirmed by XRD (X-ray diffraction).

[0041] Also, DOn X x It is preferable that the DO has high electrical conductivity. n X x Electrical transmission of Conductivity is usually 10 ―8 S / cm or more, preferably 10 ―6 S / cm or more, more preferably 1 0 ―4 S / cm or more, more preferably 10 ―2 S / cm or more, particularly preferably 10 ―1 S / cm or more, usually 10 2 On the other hand, the electron concentration of carriers is is usually 10 15 / cm 3 More than 10, preferably 16 / cm 3 More than 10, preferably 17 / cm 3 Above, more preferably 10 18 / cm 3 More than 10 21 / cm 3 Below is the DO n X x It is difficult to evaluate the electrical conductivity of the catalyst from the electrical conductivity of the entire catalyst. Yes, but DO n X x It is possible to prepare it separately and evaluate its electrical conductivity. For example, DO n X x After pressing the powder, electrodes (Pt, etc.) are vapor-deposited and used for hole measurement. Evaluation is possible by making decisions such as:

[0042] (X) The catalyst of the present invention has a stabilization structure depending on the types of A, J, and D in formula (1) and formula (2). X can be contained as an impurity to improve the semiconductor properties. From the group consisting of S, Se, Te, Sb, Bi, Pb, Cl, I, F, H, C, Si and Ge At least one kind selected from the above is used, and multiple kinds of X may be used. The amount of X is not particularly limited. Depending on the types of A, J, and D, X may not be necessary. It is preferable that the molar ratio is equal to or less than D. %, preferably 0.1 mass % or more, more preferably 0.2 mass % or more, and even more preferably Preferably 0.3% by mass or more, even more preferably 0.5% by mass or more, and particularly preferably 1% by mass or more. % by mass or more, preferably 80% by mass or less, more preferably 75% by mass or less, and even more preferably Preferably it is 70% by mass or less, even more preferably 65% ​​by mass or less, and particularly preferably 50% by mass or less. % by mass or less, and most preferably 30% by mass or less.

[0043] The molar ratio x to D is preferably 1 or less, more preferably 0.5 or less, and even more preferably It is preferably 0.2 or less, and particularly preferably 0.1 or less. Preferably 0.01 or more, more preferably 0.02 or more, and even more preferably 0.03 or more, Particularly preferably, the ratio is 0.04 or more. The balance between the supply of electrons by activation of elements and the generation of water by oxidation of hydrogen is in a preferred range.

[0044] A part of X may be introduced as a compound, and there is no particular limitation on the type or structure thereof. However, compounds such as delafossite-type sulfides and perovskite-type sulfides, carbonates, and Antimony oxides are preferably used. Also, chalcogenides such as selenides and tellurides, and calcium oxides are preferably used. A rucopyrite-type compound can also be used. When X is hydrogen, after the catalyst is synthesized, It can also be introduced by treating the material with hydrogen gas.

[0045] (n) n is the number of oxygen atoms required to satisfy the valence of D in formula (2) (molar ratio to D). Although not particularly limited, n of a catalyst that exhibits excellent performance satisfies the oxidation number of D. It is preferable that the number of oxygen atoms is slightly less than the total number of oxygen atoms, and that there is an oxygen deficiency. n is greater than 0, preferably 0.5 or more, more preferably 0.8 or more, and even more preferably 0 0.9 or more, particularly preferably 1.0 or more, and usually 1.5 or less, more preferably 1.4 It is more preferably 1.3 or less, and particularly preferably 1.25 or less.

[0046] In addition, the catalyst of the present invention according to another embodiment is a catalyst in which a p-type semiconductor oxide and an n-type semiconductor oxide are joined together. In this structure, the function of hydrogen activation and removing charge from hydrogen is p-type. Occurs on semiconductor oxides, and functions to remove oxygen from carbon dioxide and reduce carbon dioxide By this occurring on the n-type semiconductor oxide, side reactions are suppressed, and highly selective P-type and n-type semiconductor oxides can be used to obtain methanol. There are no particular limitations on the p-type semiconductor oxide as long as it exhibits the function, but it is preferable that the p-type semiconductor oxide is represented by the formula (1). The n-type semiconductor oxide is a semiconductor oxide represented by the formula (2). Preferably, it is a material.

[0047] [Catalyst Preparation] The raw materials used in the preparation of the catalyst of the present invention are usually halogen atoms of A, J, D and X. Water-soluble salts such as chlorides and nitrates, or their acidic solutions, are used. Salt, acetate, oxalate, nitrate, sulfate, as well as ammine nitrate and ethylenediamine nitrate Water-soluble raw materials that do not contain halogen elements, such as salts and ammine nitro compounds, may also be used.

[0048] There is no particular restriction on the method for preparing the catalyst, but impregnation and coprecipitation methods are preferably used. For example, a mixed aqueous solution of nitrates of the constituent elements is mixed with ammonia water, sodium carbonate solution, or hydroxide solution. A basic solution such as sodium aqueous solution or ethanolamine is added dropwise to form a mixed hydroxide. If necessary, the hydroxide is aged or hydrothermally treated, and then filtered and separated into water. After washing, it is recovered as a hydroxide gel-like precursor, dried, and then heat-treated to form a bonding material. The purpose is to obtain the following.

[0049] In the catalyst of the present invention, the bonding property of the semiconductor oxide is an important factor, so AJ a O m and DO n X x Rather than synthesizing AJ in one pot, a O m and DO n X x It is better to synthesize For example, a mixed aqueous solution of metal salts not containing D or X can be used in the above-described procedure. AJ a O m After obtaining a substance whose main component is D, the obtained substance is dissolved in an aqueous solution of D or X salt or an alcohol. D and X may be introduced later by a method such as immersion in a molten metal solution. In this way, DO n YADO n X x After obtaining a substance whose main component is A, the obtained substance is mixed with salts A and J. A and J may be introduced later by immersing them in an aqueous or alcoholic solution. No.

[0050] Furthermore, it is also preferable to add a reducing agent to adjust the mixed state of the constituent elements and the degree of oxidation-reduction. Specifically, hydrogen, ethanol, ethylene glycol, glycerin, sol Vitol, glucose, citric acid, ascorbic acid, ethanolamine, oxalic acid, acetonitrile Toluene, acetoin, hydroxylamine, hydrazine, or their salts may be used. do.

[0051] Further dehydration, decarboxylation, decomposition of remaining salts, development of crystalline structure, and improvement of bonding properties are achieved. The catalyst is preferably subjected to a heat treatment such as calcination. The temperature is preferably 100°C or higher, more preferably 150°C or higher, and even more preferably 200°C or higher. ° C. or higher, more preferably 250 ° C. or higher, and particularly preferably 300 ° C. or higher. Also, it is preferably 1200°C or less, more preferably 1100°C or less, and even more preferably The catalyst of the present invention is preferably heated to 1000°C or less, more preferably 900°C or less. It is preferable that the material is obtained through the above-mentioned process. The atmosphere during heat treatment is not particularly limited, but may be a vacuum, inert gas, air, or carbon dioxide atmosphere. In order to adjust the mixture state of the constituent elements and the degree of oxidation and reduction, heat treatment is carried out in a vacuum, inert atmosphere, etc. Heat treatment in an atmosphere of reactive gas is also preferably used. a O m In the synthesis of, for example, acid In order to adjust the degree of reduction, the precursor containing the reducing agent is first heated to 350°C or less in an air stream. The excess reducing agent is decomposed and removed by heat treatment at a temperature of 1000°C, and then nitrogen is added at a higher temperature. A method such as firing under an air flow is preferably used. By undergoing the above-mentioned baking method, the redox degree of the semiconductor oxide, especially A, is adjusted to 1+. This makes it possible to lower the firing temperature, and to obtain an oxide with a larger surface area. AJ synthesized by these methods a O m The surface area of ​​a 2 / g or more 100m 2 / g or more Below, preferably 2m 2 / g or more 80m 2 / g or less, more preferably 4m 2 / g or more 70 m 2 / g or less, more preferably 10m 2 / g or more 60m 2 / g or less.

[0052] High-temperature treatment in a hydrogen atmosphere or a mixed gas atmosphere of hydrogen and carbon dioxide before the target hydrogenation reaction or mixing with a reducing agent such as NaBH4 to partially reduce the catalyst. The reduction temperature is not particularly limited, but it is preferably 100°C or higher, more preferably 100°C or higher. Preferably 125°C or higher, more preferably 150°C or higher, particularly preferably 200°C or higher Preferably, the temperature is 800°C or lower, more preferably 700°C or lower, and even more preferably 60 It is preferably 0°C or lower, and more preferably 500°C or lower.

[0053] Other methods include physical mixing, flux method, sol-gel (dipping) method, electron de Position deposition method, photoelectrodeposition method, sputtering method, ALD (atomic layer deposition) , PLD (pulsed laser deposition), etc. can also be used. It is promising in that it is possible to obtain good materials with few defects at low temperatures. The former uses oxides and salts as raw materials, and the latter is a ball-forming method. After crushing and mixing them using a mill, they are usually heated at a temperature of 200°C or higher but less than 1200°C. The synthesis is carried out by firing in air or inert gas flow. After preparation by these methods, a method of adding further constituent elements can also be suitably used. For example, A.J. a O m After obtaining by solid-phase synthesis or hydrothermal synthesis, it is impregnated with an aqueous solution of salt containing D, By performing heat treatment or reduction treatment, D oxide or D can be introduced later. a O m The catalyst of the present invention can also be prepared by physically mixing the oxides of and D.

[0054] The catalyst after calcination or reduction prepared by the above method is crushed and mixed to improve the adhesion between particles. It is also preferable to increase the degree of mixing to improve the electrical conductivity. Furthermore, the catalyst obtained can be pressed and molded, or a carbon block can be used. A method of mixing the carbon dioxide with a conductive material such as lac is also preferably used. This ensures a route for supplying electrons to the activated sites of the cations, resulting in the promotion of methanol production. can be.

[0055] [Evaluation of the semiconducting properties of catalysts] The catalyst of the present invention is used in the direct synthesis of methanol by hydrogenation of carbon dioxide, AJ is a p-type semiconductor oxide a O m The charge obtained from hydrogen on the n-type semiconductor oxide The carbon dioxide is supplied to the activated carbon site, and the reduction is promoted. The cations have sites that can activate hydrogen and carbon dioxide, and also have electron and hole carriers. It is important that the transfer of ions occurs sufficiently quickly, i.e., the catalyst of the present invention has a sufficient semiconductor It is desirable to have a high carrier concentration and electrical conductivity.

[0056] Another reason why the catalyst of the present invention is excellent in converting carbon dioxide to methanol is that In addition, the direction of electron supply is controlled in the catalyst of the present invention. In this catalyst, the p-type semiconductor oxide AJ a O m is an n-type semiconductor oxide, DO n X x and The junction generates a so-called rectification property, and electrons flow into the DO n X x Features that are supplied unidirectionally to the side Therefore, the reduction of carbon dioxide is AJ a O m DO with more sufficient electrons n X x This occurs preferentially above the initial reduction stage, preventing CO production from occurring due to partial reduction, resulting in the formation of methanol. This means that the selectivity for AJ a O m , D.O. n X x Each of these is sufficient It is desirable for the material to have both carrier concentration and electrical conductivity.

[0057] Although the method of measuring electrical conductivity is not important, resistivity measuring instruments such as Hiresta and Loresta are also suitable. For example, a low resistance or high resistance powder probe manufactured by Mitsubishi Chemical Analytech can be used. Using the powder resistivity measurement system MCP-PD-51 equipped with a lobe unit, When a catalyst is measured under a pressure of 20 kN, its volume resistivity is typically 1.0 × 10 10 Ω·c m or less, preferably 1.0 × 10 9 Ω·cm or less, more preferably 1.0×10 8 Ω ·cm or less. The volume resistivity is 1.0×10 8 If the resistance is less than Ω·cm, the catalyst acts as a semiconductor. It shows all of these properties and can be said to have good electrical conductivity. At that time, A.J. a O m and DO n X x In the situation where the powder is bonded, the electrical conductivity of the powder can be measured. is difficult, so AJ a O m YADO n X x was synthesized independently and its electrical conductivity was used to determine the catalytic activity. The electrical conductivity of the catalyst can be evaluated. a O m The electrical conductivity of For example, when evaluated with a low or high resistance probe for powders manufactured by Mitsubishi Chemical Analytech, Using the powder resistivity measurement system MCP-PD-51 equipped with the unit, The volume resistivity under pressure is typically 1.0×10 10 Ω·cm or less, preferably 1.0× 10 9 Ω·cm or less, more preferably 1.0×10 8 Ω·cm or less. Volume resistivity is 1.0×10 8 If the capacitance is less than Ω·cm, the carrier exhibits semiconducting properties and electrical conductivity is low. It can be said that the conductivity is good.

[0058] Furthermore, the semiconductor carrier concentration and electrical conductivity can be determined by Hall measurement. For example, AJ prepared alone a O m YADO n X x After forming into a disc less than 1 mm thick Pt or the like was evaporated as a terminal, and the measurement was performed at room temperature under vacuum using a Toyo Technica Hall measurement device. When measured by the four-terminal method, the carrier concentration is usually 10 15 / cm 3 That's it, 10 22 / cm 3 Below 10, preferably 16 / cm 3That's it, 10 21 / cm 3 Below, more preferably 10 17 / cm 3 That's it, 10 20 / cm 3 More preferably, 10 18 / cm 3 End , 10 19 / cm 3 If the carrier concentration is equal to or greater than the lower limit, electrical conductivity can be obtained. This allows the charge obtained from hydrogen to be efficiently supplied to the carbon dioxide reduction site. When the arsenic concentration is equal to or less than the upper limit, the mobility can be ensured and the over-reduction reaction and the reduction to CO can be prevented. This prevents side reactions such as the formation of methyl alcohol from occurring, reducing the selectivity of the reaction to methanol. The electrical conductivity evaluated by the four-probe Hall measurement under vacuum is usually 10 ―8 S / cm More than 10, preferably ―6 S / cm or more, preferably 10 ―4 S / cm or more, and Preferably 10 ―2 S / cm or more.

[0059] Furthermore, the electrical conductivity of the oxide and the supply of electrons to carbon dioxide are mainly determined by the conduction band The proportion of conduction band electrons affects not only electrical conductivity and resistivity but also band gap. The band gap can also be predicted from various absorption and emission spectra and electrical conductivity. The band gap of the catalyst of the present invention can be calculated from the temperature dependence (slope) of the degree of Usually, it is 1 eV or more and 7 eV or less, preferably 1.5 eV or more and 6 eV or less, more preferably 2 eV or more and 5 eV or less.

[0060] In addition, the AJ required for the efficient reaction of carbon dioxide to methanol a O m From DO n X x The smooth electron transfer to AJ a O m When part of the In some cases, the work function also limits the amount of DO that reduces carbon dioxide. n X x The work function is preferably large on the side of the catalyst of the present invention or AJ a O m YADO n X x The powder of the sample prepared alone was formed into a disk shape, and It can be measured using the Kelvin probe method using a Keiki FAC-3. AJ a O m The work function of the pure Au plate was corrected to 5.11 eV. When the ion concentration is 2.0 eV or more and 6.0 eV or less, preferably 2.5 eV or more and 5.5 eV or less, The value is preferably 3.0 eV or more and 5.0 eV or less. When the fixed value was set to 5.11 eV, the DO n X x The work function of is typically 3.0 eV or more and 7.0 eV or less, preferably 3.5 eV or more and 6.5 eV or less, more preferably 4 The work function is measured by the above method with the two materials bonded together. When measured, the work function falls between the two work functions.

[0061] [Hydrogenation of oxygen-containing compounds using hydrogenation catalysts] The catalyst of the present invention is preferably used for hydrogenating oxygen-containing compounds. When carrying out the hydrogenation reaction of an oxygen-containing compound using the catalyst of the present invention, the raw material is Carbon, carbon monoxide, formyl group, ketone group, carboxylic acid group, ester group or amide group Organic or inorganic compounds having one or more carbonyl groups such as Carbon dioxide, which is abundant on Earth, inexpensive, and requires a large number of electrons for its physical transformation. The catalyst of the present invention is highly effective when the raw material is a fluorine-containing compound. The hydrogenation of carbon dioxide can be carried out in either the gas or liquid phase. The catalyst of the present invention is loaded into a reactor, and a mixed gas of carbon dioxide and hydrogen is passed through the reactor. In this case, it is acceptable to accompany the reaction with an inert gas, water, carbon monoxide, or a small amount of oxygen.

[0062] The reaction to synthesize methanol from carbon dioxide and hydrogen (carbon dioxide hydrogenation reaction) requires thermoelectric power. There is a chemical equilibrium, and the equilibrium conversion rate decreases at high temperatures. Therefore, the synthesis reaction temperature is preferably Preferably, the temperature is 50°C or higher, more preferably 100°C or higher, and even more preferably 125°C or higher. Preferably, the temperature is 400°C or lower, more preferably 300°C or lower, and even more preferably 275°C or lower. The following is the result.

[0063] In addition, increasing the pressure is advantageous because it increases the equilibrium conversion rate. Preferably, it is 0.2 MPa or more, more preferably 0.5 MPa or more, and even more preferably 1.0 MPa or more, particularly preferably 2.0 MPa or more, and more preferably 10 MPa or less. The pressure is preferably 8 MPa or less, and more preferably 6 MPa or less. When the pressure is equal to or lower than the upper limit, the reaction rate does not decrease and the productivity is improved. This can prevent the reaction rate from slowing down due to catalyst poisoning by water.

[0064] A higher hydrogen / carbon dioxide molar ratio is advantageous in terms of equilibrium. Preferably, it is 0.2 or more. More preferably, it is 0.5 or more, more preferably 1.0 or more, and even more preferably 2.0 or more. Preferably, it is 10 or less, more preferably 6.0 or less, more preferably 4.0 or less, It is more preferably 3.0 or less. By making it equal to or greater than the lower limit, the reverse reaction can be suppressed. Since the value is below the upper limit, the equipment for separating and recovering unreacted hydrogen and circulating it can be made small. It can be made into After separating the carbon monoxide and other by-products from the methanol, the carbon monoxide is The reaction mixture is converted into methanol or the like, or the unreacted carbon dioxide is then recycled to the reactor. It is also preferable to have access to the following.

[0065] In the catalyst of the present invention and the method for hydrogenating carbon dioxide using the catalyst, AJ a O m p-type semiconductors represented by DO n X x The semiconductor characteristics of the n-type semiconductor junction are expressed as By using a catalyst with By carrying out the reaction at a low temperature, which is favorable for the equilibrium, the separation of by-products can be achieved. It is also possible to reduce the burden of separation and recycling of unreacted raw materials, and to efficiently convert carbon dioxide. Therefore, it is industrially useful for synthesizing methanol from carbon dioxide. This is a convenient method.

[0066] Furthermore, the selective conversion of carbon dioxide to methanol in the hydrogenation of carbon dioxide The catalyst of the present invention is also effective in the reverse reaction of steam reforming of methanol to produce hydrogen. This reaction is similar to the methanol reaction, but it selectively produces hydrogen and carbon dioxide. This is a water reduction reaction, and is useful as a method for producing hydrogen gas for fuel cells. [Example]

[0067] The present invention will be described in more detail below. However, the present invention is not limited to these examples. It is not intended to be limited in any way. The catalyst of the present invention is loaded into a reaction tube made of glass or SUS, and a gas is passed through the reaction tube. The catalyst loading section was heated in a tubular furnace while the catalyst was being heated. The raw material gas containing hydrogen and nitrogen as an internal standard was circulated. The gas was sampled from two TCD gas sampling valves installed in series at the outlet of the reaction tube. Chromatograph (Shimadzu GC-14B (for CO2 and methanol, etc.), Shimadzu The relative chromatographic surface area with the internal standard gas nitrogen was measured by GC-8A (for hydrogen, CO, and methane). The quantity was determined from the volume ratio. The operating conditions of the gas chromatograph are as follows:

[0068] <Method for measuring organic matter> Equipment: Shimadzu TCD-GC GC-14B (medium polarity column, 3m) Measurement conditions: Column temperature programmed <Measuring method for inorganic gases> Apparatus: Shimadzu TCD-GC GC-8A (molecular sieve, 3 m) Measurement conditions: Column part 70°C

[0069] The obtained chromatographic area was corrected by each factor, and the ratio was calculated. I asked for it as below. Methanol selectivity (%) = methanol (mmol) / (methanol + carbon monoxide + methane N) x 100 The methanol production rate was calculated from the chromatographic area. ol / h / g) means the amount of methanol produced per 1 g of catalyst per 1 h.

[0070] Also, the X-ray diffraction measurement and conductivity measurement of the prepared catalyst were carried out as follows. <Powder X-ray diffraction measurement method> After finely pulverizing the sample in a mortar, it was evaluated using an X’PertProMP D manufactured by PANalytical, with an X-ray source of CuKα and a scanning range (2θ) of 5° - 90°.

[0071] <Measurement of specific surface area by BET method> The specific surface area was measured using a BELSORP II nitrogen adsorption apparatus manufactured by MicrotracBEL. After loading about 0.2 g of the sample into a dedicated cell and performing degassing treatment at 400 °C, the specific surface area was calculated by the BET method.

[0072] <Measurement method of volume resistivity> After finely pulverizing the sample in a mortar, it was evaluated using a powder resistivity measuring device. When using Loresta, a Loresta GP powder resistivity measurement system or MCP -PD-51 manufactured by Mitsubishi Chemical Analytech was used. With 1.0 g of powder, a four-probe probe, an electrode interval of 3.0 mm, an electrode radius of 0.7 mm, a sample radius of 10.0 mm, and an applied voltage limiter of 90 V, the value of the volume resistivity of the sample powder under a pressure of 20 kN was evaluated. Also, when using HighLoresta, a HighLoresta UX powder resistivity measurement system or MCP-P D-51 manufactured by Mitsubishi Chemical Analytech was used. By the double-ring electrode method, with a sample radius of 10.0 mm and 1.0 g of powder, it was evaluated by measuring with a voltage applied under a pressure of 20 kN. The density of the powder was calculated from the thickness when pressurized at 20 kN and the weight of the sample.

[0073] (Example 1) CuCrO2 was prepared based on solid-phase synthesis. Copper(I) oxide (Wako Pure Chemical Industries, Ltd.) was used. g and 3.04 g of 3N Cr2O3 manufactured by High Purity Chemicals, and then they were weighed out using an agate mortar. The mixture was then placed in a quartz firing tube and heated under nitrogen at 150 Nml min. The temperature was raised from room temperature to 1000°C in 5 hours under a stream of pure air. After sintering at 1000°C for 14 hours, the sample was then sintered. After cooling, an olive-colored CuCrO2 was obtained. Powder X-ray diffraction measurement revealed that the diffraction angle 2θ The sharp diffraction lines associated with the delafossite structure between 20° and 70° (JCPDS 39-0 247) diffraction line, and the BET specific surface area was measured and found to be 1 m 2 / g or less . Next, a CuCrO2 and ZnO catalyst was prepared as follows: Zinc acetate was dissolved in an ethanolamine / ethanol solution, and the CuCrO2 was immersed in the solution. The mixture was then heated with stirring and evaporated to dryness to obtain a solid. The solid was then loaded into a calcination tube and heated under nitrogen. After drying under air flow at 110°C for 7 hours, it was calcined at 500°C for 4 hours to obtain approximately 2 g of black ZnO / Cu. A CrO2 (10 mass%) grafted catalyst was obtained.

[0074] The catalyst after calcination was subjected to powder X-ray diffraction measurement, and the diffraction angle 2θ was 20°. Sharp diffraction lines between ~70° associated with the delafossite structure (JCPDS 39-0247) The XRD obtained showed a broad diffraction line of ZnO (JCPDS 36-1451). The chart is shown in Figure 1. Using the obtained catalyst, the hydrogenation reaction of carbon dioxide was carried out as follows. g was loaded into a reaction tube with an inner diameter of 8 mm, and the raw material gas was carbon dioxide / hydrogen / nitrogen = 8 / 48 / 6, a total of 60 Nml / min was flowed, and the temperature was raised to 300°C in about 30 minutes and maintained for 30 minutes. After pre-treatment, the gas temperature was lowered to 190°C without changing the gas composition. Approximately 25 minutes after the specified temperature was reached, the sample was A portion of the outlet gas was introduced into the gas chromatograph via a pull cock, and methanol, Carbon oxide, nitrogen, carbon monoxide and other products were analyzed. In this case, the reaction temperature is increased without changing the composition of the raw material gas, and after reaching the specified temperature, The same analysis was carried out after about 25 minutes, and the results are shown in Table 1.

[0075] Example 2 InO was prepared in the same manner as in Example 1, except that indium acetate was used instead of zinc acetate. 1. The catalyst was calcined at 500°C for 4 hours under a nitrogen stream. The catalyst after synthesis was subjected to powder X-ray diffraction measurement, and the diffraction angle 2θ was 20° to 70°. The sharp diffraction lines (JCPDS 39-0247) related to the delafossite structure between The diffraction lines of In2O3 (JCPDS 06-0416) were observed.

[0076] (Comparative Example 1) CuCrO2 prepared by solid phase synthesis in the same manner as in Example 1 was mixed with ZnO and InO 1.5 Introduced The carbon dioxide hydrogenation reaction was carried out in the same manner as in Example 1. is shown in Table 1. In addition, the powder CuCrO2 obtained by solid-phase synthesis was calcined at 1000°C for 14 hours under a nitrogen atmosphere. When X-ray diffraction measurements were performed, the delafossite structure was found between the diffraction angles 2θ 20° and 70°. It showed sharp diffraction lines (JCPDS 39-0247) related to

[0077] (Comparative Example 2) Dissolve 6.0 g of zinc nitrate hexahydrate in deionized water in a 300 cc beaker. The aqueous solution was heated to 70°C, and a 5% by mass aqueous solution of sodium carbonate was added thereto while stirring. The resulting precipitate was aged overnight, filtered, and washed with water to give a white precipitate. The resulting cake was dried in a dryer at 110°C, then loaded into a calcination tube and further After drying at 110℃ for 7 hours under air flow, it was baked at 500℃ for 4 hours to obtain about 2g of pale cream-colored cake. ZnO was obtained. The BET specific surface area was measured and found to be 11 m 2 / g. Powder X-ray diffraction measurements were performed on the ZnO obtained by firing at 500°C for 4 hours under an air flow. However, the diffraction angle 2θ between 20° and 70° was related to ZnO (JCPDS 36-1451). It showed relatively sharp diffraction lines. Using the obtained ZnO as a catalyst, the hydrogenation reaction of carbon dioxide was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0078] From the comparison between Examples 1 and 2 and Comparative Examples 1 and 2, AJ a O m / DO n X x The junction type catalyst By doing so, AJ a O m Only, DO n X x Catalytic activity not expressed by the It can be seen that methanol can be obtained with high selectivity from carbon dioxide.

[0079] Example 3 CuYO2 was prepared by solid-phase synthesis. 1.43 g of copper(I) oxide (Wako Pure Chemical Industries, Ltd.) and 2.26 g of 4N Y2O3 manufactured by Kojundo Kagaku Co., Ltd., were weighed out, and the two were mixed in an agate mortar. The mixture was placed in a quartz firing tube and sintered under nitrogen gas at 150 Nml min. The temperature was raised from room temperature to 1000°C in 5 hours, and the mixture was baked at 1000°C for 12 hours before being allowed to cool. The resulting oxide solid was removed from the firing tube, crushed and mixed in an agate mortar, and then reheated. The mixture was loaded into a quartz firing tube and heated from room temperature to 1000°C in 5 hours under a nitrogen flow of 150 Nml·min. The temperature was raised to 1000°C, and the mixture was calcined at 1000°C for 12 hours, after which it was allowed to cool, yielding brown CuYO2.

[0080] Next, a CuYO2 and ZnO catalyst was prepared as follows: Dissolve zinc oxide in an ethanolamine / ethanol solution (molar ratio 1 / 10) and add the above CuY After soaking in O2, the mixture was heated with stirring and evaporated to dryness to obtain a solid. The mixture was then dried at 110°C for 7 hours under a nitrogen stream, and then calcined at 500°C for 4 hours to produce approximately 2g of black powder. A ZnO / CuYO2 (10 mass%) junction catalyst was obtained. The catalyst after calcination was subjected to powder X-ray diffraction measurement, and the diffraction angle 2θ was 20°. Sharp diffraction lines between ~70° associated with the delafossite structure (JCPDS 39-0244) and broad ZnO (JCPDS 36-1451) diffraction lines. Using the obtained catalyst, the hydrogenation reaction of carbon dioxide was carried out in the same manner as in Example 1. The results are shown in Table 1. Shown below.

[0081] (Comparative Example 3) CuYO2 prepared by solid phase synthesis in the same manner as in Example 3 was used as a catalyst for ZnO and InO 1.5 Introduce The carbon dioxide hydrogenation reaction was carried out in the same manner as in Example 1. Shown in Table 1. In addition, the powder CuYO2 obtained by solid-phase synthesis was calcined at 1000°C for 12 hours under a nitrogen atmosphere. X-ray diffraction measurements revealed that the delafossite structure was present between the diffraction angles 2θ of 20° and 70°. The relevant sharp diffraction lines (JCPDS 39-0244) were shown.

[0082] From the comparison between Example 3 and Comparative Examples 2 and 3, DO n X x / AJ a O m To make it a junction type catalyst By A.J. a O m Only, DO n X x The catalytic performance not achieved by diacid alone was obtained. It can be seen that methanol can be obtained with high selectivity from oxidized carbon.

[0083] Example 4 As in Comparative Example 2, a cake obtained by neutralizing an aqueous zinc nitrate solution was baked under an air flow to obtain ZnO. Next, a CuCrO2 and ZnO catalyst was prepared as follows: A mixed aqueous solution of equimolar copper nitrate trihydrate and chromium nitrate nonahydrate was prepared using After immersing the ZnO in the mixed aqueous solution, it was heated with stirring and evaporated to dryness to obtain a solid. The solid was loaded into a calcination tube and dried under air flow at 110°C for 7 hours, and then heated at 500°C for 4 hours. After calcination, about 2 g of CuCrO2 / ZnO (10 mass %) junction type catalyst was obtained. Using the obtained catalyst, the hydrogenation reaction of carbon dioxide was carried out in the same manner as in Example 1. The results are shown in Table 1. Shown below.

[0084] Example 5 CuMnO2 was prepared in the same manner as in Example 4, except that manganese nitrate was used instead of chromium nitrate. A ZnO (10 mass%) junction catalyst was obtained. The obtained catalyst was used for the hydrogenation reaction of carbon dioxide. The reaction was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0085] Example 6 The procedure was the same as in Example 4, except that yttrium nitrate n-hydrate was used instead of chromium nitrate. A CuYO2 / ZnO (10 mass%) junction catalyst was obtained. The hydrogenation reaction of the raw material was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0086] Example 7 C was prepared in the same manner as in Example 4, except that gallium nitrate n-hydrate was used instead of chromium nitrate. A uGaO2 / ZnO (10 mass%) junction catalyst was obtained. The hydrogenation reaction was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0087] Example 8 C was prepared in the same manner as in Example 4, except that cerium nitrate hexahydrate was used instead of chromium nitrate. A uCeO2 / ZnO (10 mass%) junction catalyst was obtained. The hydrogenation reaction was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0088] Comparative Example 4 CuO was prepared in the same manner as in Example 4, except that only copper nitrate trihydrate was used. x / ZnO(10% Using the obtained catalyst, the hydrogenation reaction of carbon dioxide was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0089] (Comparative Example 5) CrO was prepared in the same manner as in Example 4, except that only chromium nitrate nonahydrate was used. x / ZnO(1 Using the obtained catalyst, the hydrogenation reaction of carbon dioxide was carried out as in Example 1. The results are shown in Table 1.

[0090] (Comparative Example 6) Instead of ZnO, commercially available zirconia (Saint-Gobain SZ39164 crushed material) was used. Surface area: 9 5m 2 The same procedure as in Example 4 was repeated except that CuCrO2 / ZrO2 (10 mass% / g) was used. Using the obtained catalyst, the hydrogenation reaction of carbon dioxide was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0091] From the comparison of Examples 4 to 8 with Comparative Examples 2 and 4 to 6, AJ a O m / DO n X x For the junction type catalyst By doing so, AJ a O m Only, DO n X x This resulted in catalytic performance that could not be achieved by using only Furthermore, AO m Do only n X x A catalyst bonded with AJ a O m DO n X x other than It can be seen that the catalyst bonded with carbon dioxide can produce methanol with high selectivity.

[0092] Example 9 Dissolve 4.832 g of copper nitrate trihydrate and 8.00 g of chromium nitrate nonahydrate in demineralized water. The mixture was heated to 5°C. A 10% by mass aqueous solution of NaOH was added dropwise while vigorously stirring. The pH was adjusted to 8 while the solids were precipitated. 0.72 g of ethanol was added, and the mixture was heated and stirred for 1 hour, after which the stirring was stopped, the mixture was air-cooled, and the mixture was left to stand overnight. The resulting khaki-colored hydroxide was filtered by suction using a Kiriyama funnel, then thoroughly washed with water and mixed. A mixed hydroxide cake was obtained. The obtained cake was dried at 175°C under a nitrogen stream and then air-dried. The excess reducing agent was decomposed by heating at 280°C for 10 minutes under a nitrogen stream, and then the mixture was heated at 670°C for 10 minutes under a nitrogen stream. After calcination for 2 hours, gray CuCrO2 was obtained. The obtained fired product was subjected to powder X-ray diffraction measurement. Diffraction lines related to the delafossite structure (JCPDS 39-0427) were observed between 100° and 100°. The obtained XRD chart is shown in Figure 2. In addition, the specific surface area measured by the BET method was 13 m 2 / g.

[0093] The resulting CuCrO2 and ZnO catalyst was then prepared as follows: Using this, zinc acetate was dissolved in an ethanolamine / ethanol solution (molar ratio 1 / 10), After the CuCrO2 was immersed, it was heated with stirring and evaporated to dryness to obtain a solid. The solid was loaded into a calcination tube, dried at 110°C for 7 hours under a nitrogen stream, and then calcined at 500°C for 4 hours. A black ZnO / CuCrO (10 mass%) junction catalyst was obtained. The hydrogenation reaction of carbon dioxide was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0094] Example 10 Using CuCrO2 obtained in the same manner as in Example 9, CuCrO2 and InO 1.5 The contact The solvent was prepared as follows: Indium acetate was dissolved in ethanolamine / methanone in a beaker. After dissolving the CuCrO2 in a ethanol solution (molar ratio 1 / 10), the CuCrO2 was immersed in the solution without stirring. The solid was loaded into a calcination tube and heated at 110°C under a nitrogen stream. After drying at 500°C for 7 hours, it was calcined at 500°C for 4 hours to obtain black InO 1.5 / CuCrO2(20 quality Using the obtained catalyst, the hydrogenation reaction of carbon dioxide was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0095] Example 11 Dissolve 3,624 g of copper nitrate trihydrate and 4.31 g of manganese nitrate in 70 g of demineralized water. Further, 4.0 g of NaOH was added and stirred for several hours to form a uniform slurry. The slurry was placed in an autoclave with a Teflon (registered trademark) inner cylinder, and the autoclave The toclave was placed in an oven and heated to 80°C. After 24 hours, the oven temperature was lowered. The contents were filtered, washed with water and ethanol, and dried at 110°C. After drying, it was calcined at 250°C for 2 hours under a nitrogen stream to obtain black-brown CuMnO2. The obtained fired product was subjected to powder X-ray diffraction measurement. Diffraction lines related to the delafossite structure (JCPDS 50-0860) were observed between 100° and 150°. The obtained XRD chart is shown in Figure 3. In addition, the BET specific surface area was measured and found to be 17 m 2 / g.

[0096] The resulting CuMnO2 and ZnO catalyst was then prepared as follows: Using this, zinc acetate was dissolved in an ethanolamine / methanol solution (molar ratio 1 / 10), After the CuMnO2 was immersed, it was heated with stirring and evaporated to dryness to obtain a solid. The solid was loaded into a calcination tube and dried at 110°C for 7 hours under a nitrogen stream, and then heated at 280°C under an air stream. The mixture was decomposed for 10 minutes and then calcined at 500°C under a nitrogen stream to obtain black ZnO / CuMnO2 A junction-type catalyst (10 mass%) was obtained. The obtained catalyst was used to carry out the hydrogenation reaction of carbon dioxide. The same procedure was carried out as in Example 1. The results are shown in Table 1.

[0097] (Comparative Example 7) CuCrO2 obtained in the same manner as in Examples 9 and 10 was mixed with ZnO and InO 1.5 Without introducing Using this as a catalyst, the hydrogenation reaction of carbon dioxide was carried out in the same manner as in Example 1. The results are shown in Table 1. vinegar.

[0098] (Comparative Example 8) The CuMnO2 obtained in the same manner as in Example 11 was mixed with ZnO and InO 1.5 without introducing Using this as a catalyst, the hydrogenation reaction of carbon dioxide was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0099] From the comparison of Examples 9 to 11 with Comparative Examples 7 and 8, DO n X x / AJ a O m The junction type catalyst By doing so, AJ a O m Only, DO n X x A catalytic performance not achieved by and AJ a O m As a synthesis method, salt is used as a raw material and a reducing agent or hydrothermal synthesis is used. By using this method, AJ with a large surface area can be a O m and DO n X x To join with Therefore, the methanol production rate and selectivity are high, and methanol can be produced more efficiently from carbon dioxide. It can be seen that the resulting catalyst can be synthesized.

[0100] [Table 1]

Claims

1. A semiconductor oxide represented by the following formula (1) and a semiconductor oxide represented by the following formula (2) are bonded together. A catalyst containing a substance that has been subjected to oxidation. AJ a O m (1) (In the formula (1), Component A is a minor element selected from the group consisting of Cu, Pd, Pt, Rh, Ru, Ir, and Ag. It represents at least one element, Component J is Fe, Ni, Mn, Co, Cr, Y, Sc, Ce, La, Al, Ga, and and In, The component O represents oxygen; a and m represent the molar ratios of J and O to A, respectively, and 0<a≦3 and 0.5<m≦4. It is a satisfactory number.) DO n X x (2) (In the formula (2), Component D is at least one element selected from the group consisting of In, Ga, Al, B, Zn, and Sn. It represents a type of element, The component O represents oxygen; Constituent X is P, S, Se, Te, Sb, Bi, Pb, Cl, I, F, H, C, Si and and Ge, n and x represent the molar ratios of O and X to D, respectively, and 0<n≦1.5 and 0≦x≦1. It is a satisfactory number.)

2. In X-ray diffraction measurement XRD (CuKα), the diffraction angle (2θ) ranges from 20° to 70°.

2. The catalyst according to claim 1, which has a diffraction peak characteristic of a delafossite structure. Medium.

3. Volume resistivity of 1.0 x 10 under a pressure of 20 kN at 25°C 10 Ω cm or less, Item 3. The catalyst according to item 1 or 2.

4. The method according to claim 1 or 2, which is obtained by heat treatment at 100°C or higher and 1200°C or lower. Catalysts listed.

5. 3. The catalyst according to claim 1, which is used for hydrogenating oxygen-containing compounds.

6. 6. The catalyst of claim 5, wherein the oxygen-containing compound is carbon dioxide.

7. The method according to claim 1 or 2, wherein the hydrogenation reaction of carbon dioxide is carried out under conditions of 50°C or higher and 400°C or lower. A method for producing methanol using a catalyst.

Citation Information

Patent Citations

  • JP1970016682Y1

  • JP1974017391A